Effect of Temperature and Sisal Fiber Content on the Properties of Plaster of Paris - M. ALmusawi, Aqil; S. Hussein, Thulfiqar; A. Shallal, Muhaned (International Journal of Engineering and Technology, 2018)
Recent developments in the production of ecologically friendly building composites have led to a renewed interest in the use of vegetable fibers as a reinforcement element. Traditional pure Plaster of Paris (POP) can suffer from the development of micro-cracks due to thermal expansion. Therefore, sisal fiber was studied for its potential as an ecological element to restrict and delay the development of micro-cracks in POP. Different sisal proportions of 0, 2, 4, 6, 8 and 10 wt. % of POP were used to characterize the physical and mechanical properties of POP at the ambient temperature. Then, the effects of temperatures of 25, 100, 200, 300, 400 and 500 were investigated. Results proved that the composite of 10% sisal fiber had the best mechanical properties. Also, when the fiber content was increased, the composite’s performance was enhanced, becoming better able to resist elevated temperatures. However, raising the temperature to 300or above had a negative effect on the mechanical properties, which were significantly decreased due to the degradation of the sisal fiber.
Keywords: Characterization; Effect of Temperature; Plaster of Paris; Sisal Fiber..